High-performance water-swelling acrylic acid-based material and preparation method thereof

The preparation of a high-performance water-swellable acrylic acid-based material using graphene and a long-chain silane coupling agent addresses the limitations of existing gel materials, enhancing mechanical properties and adsorption capacity for sewage treatment.

CN119119391AActive Publication Date: 2024-12-13ZIBO HONGDA AUXILIARY CO LTD

Patent Information

Application Number
CN202411616389.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-13
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

Existing gel materials exhibit low mechanical properties and limited adsorption and swelling capacity, hindering their application in sewage treatment.

Method used

A high-performance water-swellable acrylic acid-based material is prepared by modifying graphene with a reactive long-chain silane coupling agent containing an unsaturated double bond, followed by mixing with acrylic acid, acrylamide monomer, and a cross-linking agent, and freeze-drying to form a gel structure.

Benefits of technology

The material exhibits enhanced mechanical strength, porosity, and adsorption capacity, effectively removing organic pollutants like cationic dyes through van der Waals forces and chemical bonding, while being environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FXKGBDGRDAOTMHGW2FUU1IKUXH5WR4Y3EQXGNVLJ
    Figure FXKGBDGRDAOTMHGW2FUU1IKUXH5WR4Y3EQXGNVLJ
  • Figure TNWPLMMHPXETYP6HOGOHLQXBJQV5M3IICHARGZXG
    Figure TNWPLMMHPXETYP6HOGOHLQXBJQV5M3IICHARGZXG
Patent Text Reader

Abstract

The invention belongs to the technical field of gel materials, and particularly relates to a high-performance water-swelling acrylic acid-based material and a preparation method thereof. Comprising the following steps: (1) modifying graphene by adopting a silane coupling agent containing unsaturated double bonds to prepare a modified graphene dispersion liquid; (2) sequentially adding acrylic acid, an acrylamide monomer and a cross-linking agent into the modified graphene dispersion liquid, then adding an initiator, and reacting to obtain a gel mixed solution; and (3) freeze-drying the gel mixed solution to obtain the high-performance water-swelling acrylic acid-based material. The gel material is uniform in pore structure and high in mechanical strength. Physical adsorption can be carried out by taking Van der Waals force or electrostatic attraction force as adsorption driving force through a pore structure, and chemical adsorption can also be carried out by taking chemical bond force or hydrogen bond interaction as adsorption driving force through functional groups on the graphene and the acrylic polymer, so that organic pollutants such as cationic dyes and the like can be effectively and quickly removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gel materials, and in particular relates to a high-performance water-swellable acrylic acid-based material and a preparation method thereof. Background Art

[0002] Water is the most important resource for human beings and other organisms. However, with the frequent production and life activities of human beings, the release of some harmful substances will cause water pollution, which will not only have a negative impact on species living in water, but also have a negative impact on a wider range of natural organisms, causing serious health and environmental problems. The most prominent pollutants are heavy metals and organic pollutants. Heavy metals include lead, cadmium, copper, nickel, etc., which will be produced and released into the environment through various industrial production processes and other human activities. Heavy metal ions have become one of the main sources of water pollutants due to their persistence and toxicity, and are a huge threat to all biological organisms and the entire environment. At the same time, there are many types of organic waste. For just one category, dyes, global chemical companies use nearly 1 million tons of dyes each year, of which more than 10% of the waste is discharged as wastewater. Dyes generally have complex and stable chemical structures, which are difficult to degrade and easy to accumulate in large quantities, which will also have long-term effects on the environment and human health. In addition to heavy metals and dyes, oily wastewater is also a major problem in water pollution. Oil pollution comes from a wide range of sources, including food, textiles, oil and gas, petrochemical processing and metal processing industries. A large amount of waste oil and wastewater is discharged into water bodies. Due to the characteristics of oil, it is easy to penetrate into the soil, so oily wastewater pollution is more likely to affect drinking water, groundwater and seawater through infiltration. Oily wastewater contains petroleum hydrocarbons, phenols and polycyclic aromatic hydrocarbons, which can slow down the growth of plants and animals. Cause mutations in the human body and increase the risk of cancer. In addition, some radioactive substances, antibiotics, pesticides and other pollutants have also caused a lot of water pollution problems.

[0003] Among them, methylene blue is a phenothiazine salt, which is relatively stable in the air. It appears as crystals or powders. It is soluble in water and ethanol, but insoluble in ethers. Methylene blue is dark green at room temperature with a bronze luster. Its aqueous solution is blue, alkaline and highly toxic. Entering the human body can cause abdominal pain, dizziness, headache and other adverse symptoms. Methylene blue is also reducing and oxidizing, so it is often used as a dye for fabrics, paper, etc.; and is used as a chemical indicator and biological indicator for drug research. Methylene blue is very harmful to the environment and is a representative dye pollutant among organic pollutants in water bodies. The hazards of water pollution caused by organic dyes have always attracted the attention of scientific researchers, and the methods for treating organic dye wastewater have made certain progress.

[0004] Hydrogel is a three-dimensional mesh material consisting of a cross-linked network and interstitial spaces filled with water. Due to its excellent water absorption and water retention ability and certain mechanical strength, it is widely used in many functional materials and daily commodities, especially in the fields of biomedicine, energy storage, environmental engineering, agriculture, sensors, etc. At the same time, the rich chemical composition of the gel and the large amount of internal space provide sufficient space for its modification and compounding, and this further modification of the gel structure and composition can often give it rich functions and "intelligent" characteristics. At present, the development and research of gel has become a hot topic in the field of sewage treatment. However, the mechanical properties of the gel materials currently prepared are low, and the adsorption and swelling capacity is limited, which limits the application of gel materials in the field of sewage treatment. Summary of the invention

[0005] In order to overcome the problems of low mechanical properties and limited adsorption and swelling capacity of existing gel materials, the present invention provides a high-performance water-swellable acrylic acid-based material and a preparation method thereof.

[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene is modified by using a silane coupling agent containing an unsaturated double bond to prepare a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:(0.1-0.6); the molecular formula of the silane coupling agent containing an unsaturated double bond is CH2=CH-X-Si-Y3, X is a straight-chain alkyl group with 6-16 carbon atoms, and Y is an alkoxy group with 1-4 carbon atoms; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 45-80°C for 2-5h to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500: (150-200): (5-15); (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0007] As a polymer with water absorption properties, hydrogels are widely used in the field of pollutant absorption and treatment. They have good adsorption capacity, low cost, versatility and regeneration potential, and are a good choice for sewage treatment. In previous work, the inventors used POSS and graphene oxide as modified reinforcing fillers to prepare water-swellable acrylic-based gel materials (CN118772325 A). However, due to the strong hydrophobicity of POSS, the adsorption performance of the gel is poor; and graphene oxide has many surface defects and low mechanical strength, which is not conducive to the improvement of the mechanical properties of the gel material, and the water absorption and swelling stability is poor. In order to solve the above problems, the present invention uses graphene as an enhanced adsorption material. Compared with graphene oxide, graphene has fewer surface defects, greater elasticity and rigidity, which is conducive to the stability of the structure of the gel after water absorption and swelling, and prevents the occurrence of breakage. However, it is precisely because of the few defects of graphene that its water dispersibility is poor and its compatibility with acrylic polymers is low. The existing technology generally uses short carbon chain silane coupling agents such as KH550 and KH560 to modify graphene to prevent graphene from agglomerating and improve its compatibility with polymers. However, short carbon chain silane coupling agents have a short chain length and no active groups, so they cannot participate in the polymerization reaction, and the improvement effect is limited.

[0008] The present invention adopts a reactive long-chain silane coupling agent with a molecular formula of CH2=CH-X-Si-Y3 to modify graphene. The long-chain alkyl group gives it good flexibility and water resistance. This unique "two-terminal group" structure enables the long-chain carbon chain silane coupling agent to build a "molecular bridge" between graphene and acrylic polymer, improve the performance of the composite material and increase the connection strength. The alkoxy group on one side of the long-chain silane coupling agent can react with active groups such as hydroxyl or carboxyl on the surface of graphene to form a stable chemical bond, thereby improving the dispersion stability of graphene; at the same time, it can also improve the interface compatibility of graphene and acrylic polymer materials, improve the bonding force between graphene and polymers, thereby significantly enhancing the mechanical properties of the material such as tensile strength. In addition, the long carbon chain structure of the coupling agent can cause molecular cross-linking and entanglement between different coupling agent molecules to form a network structure similar to a gel structure, which not only improves the mechanical properties of the gel material, but also improves the porosity of the gel material, which is conducive to the improvement of adsorption performance. The mass ratio of graphene to the silane coupling agent containing unsaturated double bonds is 1: (0.1-0.6); when the amount of the silane coupling agent containing unsaturated double bonds is too small, the graphene dispersion ability is insufficient; when the amount of the silane coupling agent containing unsaturated double bonds is too large, the gel material will be excessively cross-linked, the elastic properties will be reduced, and it will be not conducive to the improvement of adsorption capacity.

[0009] Furthermore, the silane coupling agent containing an unsaturated double bond in step (1) is at least one of octenyltrimethoxysilane, octenyltriethoxysilane, nonenyltrimethoxysilane, nonenyltriethoxysilane, decenyltrimethoxysilane, decenyltriethoxysilane, undecenyltrimethoxysilane, undecenyltriethoxysilane, dodecenyltrimethoxysilane, dodecenyltriethoxysilane, tetradecenyltrimethoxysilane, tetradecenyltriethoxysilane, hexadecenyltrimethoxysilane, hexadecenyltriethoxysilane, octadecenyltrimethoxysilane and octadecenyltriethoxysilane; further, the silane coupling agent containing an unsaturated double bond is a combination of coupling agents having straight-chain alkyl groups of different lengths (i.e., different numbers of carbon atoms in X).

[0010] Furthermore, the specific process of modifying graphene with a silane coupling agent containing unsaturated double bonds in step (1) is: dispersing graphene and the silane coupling agent containing unsaturated double bonds in a mixed solution of deionized water and ethanol; and then reacting at 70-90° C. for 3-6 hours to obtain a modified graphene dispersion.

[0011] Furthermore, the graphene concentration in the mixed solution is 0.1-0.4 g / L.

[0012] Furthermore, the volume ratio of deionized water to ethanol in the mixed solution is 1:(1-3).

[0013] Furthermore, in step (2), the cross-linking agent is N,N'-methylenebisacrylamide; and the initiator is at least one of ammonium persulfate, potassium persulfate and sodium persulfate.

[0014] Furthermore, in step (2), the mass ratio of acrylic acid, crosslinking agent, and initiator is 500: (2-10): (3-5). Furthermore, the mass ratio of acrylic acid, crosslinking agent, and initiator is 500: (4-6): (3-5). By adjusting the amount of crosslinking agent, the crosslinking degree of the acrylic acid polymer is adjusted, and the porosity and adsorption capacity of the gel material are improved while ensuring the mechanical properties of the gel material.

[0015] Furthermore, the reaction temperature in step (2) is 55-65° C. By adjusting the reaction temperature, the dispersion of graphene in the gel material can be promoted and the mechanical properties of the material can be improved; the reaction rate can also be controlled, which is conducive to the formation of a high-porosity gel structure.

[0016] Furthermore, in step (2), the mass ratio of acrylic acid, acrylamide monomer, and graphene is 500: (150-200): (10-15). Graphene plays a role in strengthening the skeleton in the gel structure and can also improve the porosity of the gel. However, as a nano-scale filler, when it is used in excessive amounts, it is prone to agglomeration and uneven dispersion, resulting in reduced mechanical properties of the gel material.

[0017] On the other hand, the present invention also provides a high-performance water-swellable acrylic-based material. The pore structure of the gel material is relatively uniform and has high mechanical strength. Since the graphene material has a large specific surface area, it can form more and regular pores with the acrylic polymer; and the graphene and acrylic polymer themselves have rich oxygen-containing functional groups, which can be combined with the methylene blue dye molecules with multiple benzene rings through various forces. It can be seen that the gel material of the present invention can be physically adsorbed through the pore structure with van der Waals force or electrostatic attraction as the adsorption driving force, and can also be chemically adsorbed through the functional groups on the graphene and acrylic polymer with chemical bonding force or hydrogen bonding as the adsorption driving force, which can effectively and quickly remove organic pollutants such as cationic dyes.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention uses a reactive long-chain silane coupling agent with a molecular formula of CH2=CH-X-Si-Y3 to modify graphene, and the long-chain alkyl group gives it good flexibility and water resistance. This unique "two-terminal group" structure enables the long carbon chain silane coupling agent to build a "molecular bridge" between graphene and acrylic polymer, thereby improving the performance of the composite material and increasing the connection strength. The gel material of the present invention can be physically adsorbed by using van der Waals force or electrostatic attraction as an adsorption driving force through the pore structure, and can also be chemically adsorbed by using chemical bonding force or hydrogen bonding action as an adsorption driving force through the functional groups on graphene and acrylic polymer, so that organic pollutants such as cationic dyes can be effectively and quickly removed. The water-swellable acrylic-based material is supplied in a solid form, and the product does not contain water and organic solvents, thereby avoiding environmental pollution and energy consumption problems in the production, storage, transportation and use links, and has broad application prospects. DETAILED DESCRIPTION

[0019] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0020] Example 1 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 70°C for 6 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.1; the silane coupling agent containing an unsaturated double bond is undecenyltriethoxysilane; the graphene concentration in the mixed solution is 0.1 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:1; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 50°C for 5 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:150:10; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:4:3; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0021] Example 2 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 90°C for 3 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.6; the silane coupling agent containing an unsaturated double bond is undecenyltrimethoxysilane; the graphene concentration in the mixed solution is 0.4 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:3; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 75°C for 2 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:200:15; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:6:5; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0022] Example 3 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 70°C for 6 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.1; the silane coupling agent containing an unsaturated double bond is octenyltrimethoxysilane; the graphene concentration in the mixed solution is 0.4 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:1; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 65°C for 3 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:150:15; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:4:5; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0023] Example 4 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 75°C for 5 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.2; the silane coupling agent containing an unsaturated double bond is octenyltriethoxysilane; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 58°C for 3 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:160:12; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:4.5:3.5; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0024] Example 5 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 85°C for 5 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.5; the silane coupling agent containing an unsaturated double bond is octenyltrimethoxysilane; the graphene concentration in the mixed solution is 0.3 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 62°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:180:14; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:5.5:4.5; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0025] Example 6 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 80°C for 4 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.4; the silane coupling agent containing an unsaturated double bond is a mixture of octenyltrimethoxysilane and undecenyltrimethoxysilane in a mass ratio of 1:1; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 60°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:170:13; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:5:4; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0026] Example 7 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 80°C for 4 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.4; the silane coupling agent containing an unsaturated double bond is a mixture of octenyltrimethoxysilane and undecenyltrimethoxysilane in a mass ratio of 1:1; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 60°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:170:13; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:2:4; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0027] Example 8 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 80°C for 4 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.4; the silane coupling agent containing an unsaturated double bond is a mixture of octenyltrimethoxysilane and undecenyltrimethoxysilane in a mass ratio of 1:1; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 60°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:170:13; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:10:4; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0028] Example 9 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 80°C for 4 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.4; the silane coupling agent containing an unsaturated double bond is a mixture of octenyltrimethoxysilane and undecenyltrimethoxysilane in a mass ratio of 1:1; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 60°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:170:5; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:5:4; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0029] Example 10 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 80°C for 4 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.4; the silane coupling agent containing an unsaturated double bond is octenyltrimethoxysilane; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 60°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:170:13; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:5:4; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0030] Embodiment 11 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 80°C for 4 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.4; the silane coupling agent containing an unsaturated double bond is undecenyltrimethoxysilane; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 60°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:170:13; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:5:4; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0031] Comparative Example 1 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 80°C for 4 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.4; the silane coupling agent containing an unsaturated double bond is allyltrimethoxysilane; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 60°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:170:13; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:5:4; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0032] Comparative Example 2 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 80°C for 4 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:1; the silane coupling agent containing an unsaturated double bond is a mixture of octenyltrimethoxysilane and undecenyltrimethoxysilane in a mass ratio of 1:1; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 60°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:170:13; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:5:4; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0033] Comparative Example 3 A method for preparing a high-performance water-swellable acrylic acid-based material comprises the following steps: (1) Graphene and a silane coupling agent containing an unsaturated double bond are dispersed in a mixed solution of deionized water and ethanol; then reacted at 80°C for 4 hours to obtain a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:0.4; the silane coupling agent containing an unsaturated double bond is a mixture of octenyltrimethoxysilane and undecenyltrimethoxysilane in a mass ratio of 1:1; the graphene concentration in the mixed solution is 0.2 g / L; the volume ratio of deionized water to ethanol in the mixed solution is 1:2; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 60°C for 4 hours to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500:170:20; the cross-linking agent is N,N'-methylenebisacrylamide; the initiator is ammonium persulfate; the mass ratio of acrylic acid, cross-linking agent and initiator is 500:5:4; (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

[0034] Performance Test: Tensile properties: The tensile breaking strength of acrylic-based materials after water swelling was tested using a universal tensile testing machine.

[0035] Equilibrium swelling ratio: Accurately weigh the mass of high-performance water-swellable acrylic-based material m0, immerse it in an aqueous solution, take out the gel sample after reaching swelling equilibrium, and use filter paper to absorb the surface moisture, then weigh the absorbed gel mass m1, and use the formula (m1-m0) / m0 to get the equilibrium swelling ratio of the gel. Equilibrium adsorption capacity: Use distilled water to prepare a methylene blue solution (ρ0) with a mass concentration of 360 mg / L, accurately weigh the mass of high-performance water-swellable acrylic-based material m0, immerse it in a methylene blue solution with a volume of V, and measure the methylene blue concentration in the solution with a UV-spectrophotometer at regular intervals until the methylene blue concentration (ρ1) remains unchanged, and use the formula (ρ0-ρ1)*V / m0 to get the equilibrium adsorption capacity of the gel.

[0036] As can be seen from Table 1, the use of graphene as an enhanced adsorption material has fewer surface defects than graphene oxide, and has greater elasticity and rigidity, which is beneficial to the stability of the structure after the gel absorbs water and expands, and prevents the occurrence of breakage. Comparative Example 1 shows that compared with short carbon chain silane coupling agents, the long carbon chain structure of the coupling agent can cause molecular cross-linking and entanglement between the coupling agent molecules, forming a network structure similar to the gel structure, which not only improves the mechanical properties of the gel material, but also improves the porosity of the gel material, which is beneficial to improving the adsorption performance of organic pollutants such as rhodamine. Comparative Example 2 shows that when the amount of silane coupling agent containing unsaturated double bonds is too much, it will cause excessive cross-linking of the gel material, reduce elastic properties, and be unfavorable for improving adsorption capacity. At the same time, Comparative Example 3 shows that when graphene is used as a nano-scale filler, it is easy to agglomerate when it is used in too much, and the dispersion is uneven, resulting in reduced mechanical properties and adsorption properties of the gel material.

[0037] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a high-performance water-swellable acrylic acid-based material, characterized in that: The following steps are involved: (1) Graphene is modified by using a silane coupling agent containing an unsaturated double bond to prepare a modified graphene dispersion; the mass ratio of graphene to the silane coupling agent containing an unsaturated double bond is 1:(0.1-0.6); the molecular formula of the silane coupling agent containing an unsaturated double bond is CH2=CH-X-Si-Y3, X is a straight-chain alkyl group with 6-16 carbon atoms, and Y is an alkoxy group with 1-4 carbon atoms; (2) Add acrylic acid, acrylamide monomer and cross-linking agent to the modified graphene dispersion in sequence, stir evenly, then add initiator, and react at 45-80°C for 2-5h to obtain a gel mixed solution; the mass ratio of acrylic acid, acrylamide monomer and graphene is 500: (150-200): (5-15); (3) Freeze-drying the gel mixture solution to obtain a high-performance water-swellable acrylic-based material.

2. The method for preparing a high-performance water-swellable acrylic-based material according to claim 1, characterized in that: The silane coupling agent containing unsaturated double bonds in step (1) is at least one of octenyltrimethoxysilane, octenyltriethoxysilane, nonenyltrimethoxysilane, nonenyltriethoxysilane, decenyltrimethoxysilane, decenyltriethoxysilane, undecenyltrimethoxysilane, undecenyltriethoxysilane, dodecenyltrimethoxysilane, dodecenyltriethoxysilane, tetradecenyltrimethoxysilane, tetradecenyltriethoxysilane, hexadecenyltrimethoxysilane, hexadecenyltriethoxysilane, octadecenyltrimethoxysilane and octadecenyltriethoxysilane.

3. The method for preparing a high-performance water-swellable acrylic-based material according to claim 1, characterized in that: The specific process of modifying graphene with a silane coupling agent containing unsaturated double bonds in step (1) is as follows: dispersing graphene and the silane coupling agent containing unsaturated double bonds in a mixed solution of deionized water and ethanol; and then reacting at 70-90° C. for 3-6 hours to obtain a modified graphene dispersion.

4. The method for preparing a high-performance water-swellable acrylic-based material according to claim 3, characterized in that: The graphene concentration in the mixed solution is 0.1-0.4 g / L.

5. The method for preparing a high-performance water-swellable acrylic-based material according to claim 3, characterized in that: The volume ratio of deionized water to ethanol in the mixed solution is 1:(1-3).

6. The method for preparing a high-performance water-swellable acrylic-based material according to claim 1, characterized in that: In step (2), the cross-linking agent is N,N'-methylenebisacrylamide; and the initiator is at least one of ammonium persulfate, potassium persulfate and sodium persulfate.

7. The method for preparing a high-performance water-swellable acrylic-based material according to claim 1, characterized in that: In step (2), the mass ratio of acrylic acid, crosslinking agent and initiator is 500:(2-10):(3-5).

8. The method for preparing a high-performance water-swellable acrylic-based material according to claim 1, characterized in that: The reaction temperature in step (2) is 55-65°C.

9. The method for preparing a high-performance water-swellable acrylic-based material according to claim 1, characterized in that: In step (2), the mass ratio of acrylic acid, acrylamide monomer and graphene is 500: (150-200): (10-15).

10. A high performance water-swellable acrylic-based material, characterized in that: The high-performance water-swellable acrylic acid-based material is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Hydrogel surface modification method and hydrogel with high water-retaining property

    CN115073771A

  • Water-swelling acrylic gel material and preparation method thereof

    CN118772325A

  • Graphene hydrogel and graphene aerogel as well as preparation methods therefor and applications thereof

    WO2016037565A1

Cited By

  • Cashmere and graphene fiber blending process

    CN120291348A

  • A high-performance ion exchange resin material and preparation method thereof

    CN120393974B

  • Modified neoprene latex and preparation method thereof

    CN121779629A